2016
DOI: 10.1161/jaha.116.003192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the American Heart Association's Impact Goals (Life's Simple 7) With Risk of Chronic Kidney Disease: Results From the Atherosclerosis Risk in Communities (ARIC) Cohort Study

Abstract: BackgroundAs part of its 2020 Impact Goals, the American Heart Association developed the Life's Simple 7 metric for cardiovascular health promotion. The relationship between the Life's Simple 7 metric and incident chronic kidney disease (CKD) is unknown.Methods and ResultsWe estimated the association between Life's Simple 7 and incident CKD in 14 832 Atherosclerosis Risk in Communities study participants. Ideal levels of Life's Simple 7 health factors were the following: nonsmoker or quit >1 year ago; body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 28 publications
5
65
1
Order By: Relevance
“…For dietary patterns in Life's Simple 7, some investigators raised a concern that adherence to the 5 AHA dietary recommendations is challenging 25. In fact, in our study as well as previous ones, the prevalence of ideal diet patterns is low (<1%–6%) 17, 18, 26, 27, 28. This might partially explain no significant association, even with incident MI, an analysis with much higher statistical power than the analysis after incident MI.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…For dietary patterns in Life's Simple 7, some investigators raised a concern that adherence to the 5 AHA dietary recommendations is challenging 25. In fact, in our study as well as previous ones, the prevalence of ideal diet patterns is low (<1%–6%) 17, 18, 26, 27, 28. This might partially explain no significant association, even with incident MI, an analysis with much higher statistical power than the analysis after incident MI.…”
Section: Discussioncontrasting
confidence: 50%
“…25 In fact, in our study as well as previous ones, the prevalence of ideal diet patterns is low (<1%-6%). 17,18,[26][27][28] This might partially explain no significant association, even with incident MI, an analysis with much higher statistical power than the analysis after incident MI. Despite arguments for the so-called obesity paradox (ie, obesity increasing the risk of incident MI but decreasing the risk of adverse outcomes after MI), [29][30][31] ideal BMI at middle age was robustly associated with better prognosis after incident MI at later life in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Fifteen studies (79,998 participants) reported incident CKD (22)(23)(24)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) across eight datasets (22,23,27,29,30,32,34,36). Four studies reported data from the Tehran Lipid and Glucose Study 2006Study -2008, one study reported three different analyses from the Tehran Lipid and Glucose Study 2009-2011 (27), four studies reported data from the Atherosclerosis Risk in Communities study (24,33,34,39), and two studies reported data from the Framingham Offspring Cohort (28,29). In a meta-analysis including eight studies from the eight eligible cohort datasets (31,410 participants; mean, 7.1 years follow-up), adherence to a healthy dietary pattern was associated with lower odds of incident CKD (OR, 0.70; 95% CI, 0.60 to 0.82; I 2 =51%) with moderate certainty of evidence (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…9, 11, 2833 Among 3,107 African American participants of the ARIC study who were followed for a median 18.7 years, the age-sex adjusted CVD incidence rates per 1,000 person years (95% CI) for participants with 0, 1, 2, 3, 4 and ≥5 ideal Life’s Simple 7 components were 40.4 (32.0–51.5), 25.3 (22.4–28.6), 16.9 (15.0–19.1), 14.2 (12.2–16.5), 8.7 (6.6–11.5) and 3.3 (1.5–7.4), respectively. 29 Having more Life’s Simple 7 components in the ideal range has also been associated with a lower risk for incident cognitive impairment 34, 35 , venous thromboembolism 36 , vascular and non-vascular death, 28 end-stage renal disease 37 and CKD 38 in African Americans.…”
Section: Discussionmentioning
confidence: 99%